Penerapan Model Project Based Leraning Melalui Lesson Study dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Syahidi, Khaerus; Triandini, Widya; Mardi, Eko Septi; Fartina, Fartina (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2023)
This research was conducted because there was still a low level of critical thinking skills of students in learning Physics. The purpose of this study was to see the improvement of students' critical thinking skills through the application of project-based learning model. The subject of the research is class XI MIPA 2 at SMAN 3 Selong which consists of 18 students. The instruments in this study consisted of observation sheets, student worksheets, and critical thinking skills test sheets. From the results of the study it was found that the critical thinking skills of students showed an increase in each cycle with the application of the Project Based Learning model. Thus it was concluded that this Classroom Action Research was categorized as reaching the target in the second cycle.